Asupan Zat Gizi Makro Sarapan, Selingan Pagi, dan Makan Siang Kaitannya dengan Kelelahan Kerja pada Guru - Hikmiyah Harisma Dewi; Farapti Farapti; Dominikus Raditya Atmaka (Universitas Airlangga, 2024)
Background: Work fatigue is a condition that arises due to high activity carried out by individuals until they are no longer able to do it. Teachers are a group of workers prone to lack energy due to the high workload and busy working hours. Objectives: to analyze the relationship between the consumption of breakfast, morning snacks, and lunch with the level of work fatigue in elementary school teachers in full-day schools in the city of Surabaya. Methods: This research used a cross-sectional design on 88 elementary school teachers at SD Muhammadiyah 04 and Luqman Al-Hakim Surabaya. Sample selection used the cluster random sampling method. Lunch consumption data was taken using the 24-hour food recall method. Work fatigue was measured using the Subjective Self Rating Test (SSRT) questionnaire. Analysis of the relationship between variables uses the Chi-square correlation test with a significance level of ð”›¼ = 0.05. Results: The results of the study showed that there was no relationship between the consumption of breakfast, morning snacks, and lunch with the level of work fatigue. Most teachers felt they were not tired (71.6%) and only a tiny percentage felt tired (28.4%). Teachers' overall macronutrient intake is still less than the required standards. The energy contribution of breakfast, morning snacks, and lunch is 16.3% from 25%, 6.4% from 10%, and 18% from 30% respectively. Conclusions: There is no relationship between consumption of breakfast, morning snacks and lunch with the level of work fatigue. There needs to be health promotion regarding work fatigue and teachers getting used to eating breakfast at 07.00-08.00 so that energy reserves in the body can last longer for teaching.